2011
DOI: 10.4028/www.scientific.net/amr.287-290.1003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Active Alumina on Sintering Behavior of Andalusite Powder

Abstract: The effect of active alumina on the sintering behavior of andalusite powder was studied. The results revealed that the addition of active alumina delayed the decomposition of andalusite and primary mullitization, beginning temperature of secondary mullitization was about 1350°C. The temperature at which the effect of expansion of the secondary mullitization emerged was about 1400°C, and the expansion effect of secondary mullitization did not yet complete at 1600°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…[1][2][3] For the perfect thermal stability at high temperature, andalusite ceramic meets the requirement of materials used in the solar power system. According to Li et al's research, 4 andalusite would decompose and convert into primary mullite (83 wt-%) along with silica-rich glass phase (17 wt-%) with volume expansion of 3-5% at elevated temperature. However, the excessive silica-rich glass phase produced by primary mullite is not benefit for the high temperature performance of the sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] For the perfect thermal stability at high temperature, andalusite ceramic meets the requirement of materials used in the solar power system. According to Li et al's research, 4 andalusite would decompose and convert into primary mullite (83 wt-%) along with silica-rich glass phase (17 wt-%) with volume expansion of 3-5% at elevated temperature. However, the excessive silica-rich glass phase produced by primary mullite is not benefit for the high temperature performance of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a variety of alumina-containing raw materials were introduced to react with silica-rich glass phase in order to form the stable mullite phase by many researchers. Li et al 4 investigated the effect of active alumina on sintering behaviour of andalusite powder and revealed that the secondary mullitisation was taken place at 1350°C, and the reaction temperature was independent on the amount of the added active alumina. It was reported 5 that a dense thin substrate was fabricated by tape casting of andalusite with alumina for the development of thin film solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Jianfeng Wu, et al [6] prepared an innovative thermal storage material by using in-situ synthesized cordierite combined with andalusite at 1400 °C, however, the apparent porosity of the samples was 22.95% and the bulk density was only 2.14 g•cm -3 . The effect of active alumina on the decomposition of andalusite powders during sintering process was studied by Liusheng Li [7] . The results revealed that the addition of active alumina delayed the decomposition of andalusite and primary mullitization, meanwhile, the reaction of secondary mullitization did not yet complete at 1600 °C.…”
Section: Introductionmentioning
confidence: 99%